KINERJA KARYAWAN DPUPR KABUPATEN SRAGEN - Siti Qomariyah; Praptiestrini (Economics, Social, and Humanities Journal (Esochum), 2021)
This study aims to determine the effect of the application of accounting information systems, the use of information technology, and internal control on the performance of DPUPR Sragen Regency employees, either partially and simultaneously. This research was conducted at DPUPR Sragen Regency. The population in this study were 120 employees. The research sample of 60 respondents with purposive sampling technique. Data instruments in the form of a questionnaire. Data analyzed with inductive statistical techniques. Hypothesis tested by multiple regression analysis models, t test and F test. Regression test results obtained Y = -2,981 + 0,415 X1 + 1,073 X2 + 0,453 X3. The research results were: application of accounting information systems, utilization of information technology, and internal control influenced employee performance, either partially and simultaneously.